Trading firms and trading costs in services: Firm-level analysis - Rouzet, Dorothée (OECD Trade Policy Papers, 2017)
This report presents evidence on how services trade restrictions influence the decisions and performance of firms engaged in international markets, drawing on micro-data from Belgium, Finland, Germany, Italy, Japan, Sweden, the United Kingdom, and the United States. It first describes the patterns of services exports and affiliate sales at the firm level, uncovering a number of stylised facts about the firms engaged in international trade in services, their choices of modes of supply and the links between services trade and manufacturing activities. The report then relates these outcomes to services trade policy barriers in destination markets as measured by the OECD STRI. It demonstrates that complex and restrictive regulatory environments limit the volume of services that firms are able to trade as well as the number of firms that engage with those markets. Hence services trade restrictions reflect not only ad valorem trade costs, but also fixed and sunk costs. Such barriers do not affect all firms equally. Restrictive services trade regulations disproportionately discourage SMEs. Size, productivity and previous exporting experience appear to be decisive factors in dealing with at-the-border and behind-the-border trade barriers. Finally, the cost of regulatory compliance is lower for foreign-owned firms with headquarters located in the export destination country and for firms that trade bundles of services and manufacturing products, than it is for pure services exporters